Roles of the histone methyltransferase G9a in the development and differentiation of mesenchymal tissues - Hisashi Ideno; Kazuhisa Nakashima; Akira Nifuji (Japanese Society of Physical Fitness and Sports Medicine, 2015)
The expression of cell lineage-specific genes during cell differentiation and development is regulated by lineage-specific transcription factors. Recent studies have revealed that epigenetic mechanisms, including post-translational modifications in histone proteins and DNA methylation, play important roles in cell lineage determination and further differentiation. Many different post-translational modifications of histone proteins have been identified to date. For example, modifications at the N-terminal ninth lysine residue of histone H3 (H3K9) are associated with the level of gene expression and local chromatin structure. H3K9 is known to have un-, mono-, di-, and trimethylation states, and these methylated states are determined by six H3K9 methyltransferases in mammals. Among these H3K9 methyltransferases, G9a is responsible for mono- and dimethylation of H3K9. G9a-null mice showed embryonic lethality, indicating its critical roles in cell differentiation, organogenesis, and development. Indeed, studies of G9a conditional deletion in vivo and G9a-deficient cells in vitro have suggested that G9a is a multifunctional protein in various cell types. This short review summarizes recent findings regarding the effects of G9a function on the development of mesenchymal tissues, such as muscle, adipose, and skeletal tissues.